Corporate Farming as an Effort to Increase Rice Farming Production in Central Java - Muhammad Joni Iskandar; Rini Endang Prasetyowati; Dwi Haryati Ningsih (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to estimate production factors and technical efficiency of rice farming using the corporate farming model. The research location was determined purposively in Sukoharjo Regency, Central Java. The research sample is 51 corporate farmers determined by census. The analytical method uses the stochastic frontier 4.1.C computational program with the Maximum Likelihood Estimation (MLE) method. The estimation results show that the factors that influence rice production are land area, Urea fertilizer and NPK fertilizer. While the value of the technical efficiency of rice farming in the corporate farming model is 0.75 (75%). Farmers still have the opportunity to increase their efficiency by 25%.